Knowledge Management Process of Learning Resources in Schools: Participatory Action Research - Janjamroon, Wichai; Phosirikul, Sukit; Thongkham, Worachai; Songsang, Wiraporn; Rotbamroe, Bunchakkrawan (Rajapark Journal, 2022)
The objective of this research was to develop the knowledge management process of learning resources in Ban Nongkung Wittayakarn School, Khon Kaen Primary Educational Service Area 1. Research participants comprised 1 administrator, 6 1-3 level high school teachers, 50 1-3 level high school students, 50 parents, 7 basic education committee members, 1 district agricultural official, and 1 subdistrict administrative organization official, totaling 115 people. Research tools comprised 1) checklist form, 2) semi-structured interview form, and 3) general meeting record form. Data analysis employed frequency and percentage statistics, and content analysis. Research findings indicate the community learning resources management process consists of 1) identifying the needed intelligence capital or knowledge; 2) creating intelligence capital or seeking benefits from existing resources, adding knowledge from outside organizations, learning from others’ success, benchmarking and collecting documents, information, and knowledge according to interested groups; 3) seeking and storing organization knowledge systematically, such as in document form, computer data file, CD, and website platform; and 4) sharing, exchanging, distributing, disseminating, and transferring knowledge; and 5) utilizing or applying knowledge.